A Case of Early Intentional Bilingualism: A Close Examination of Context and Practices - Kayadibli-Oğuz , Serra; Çamlıbel-Acar, Zeynep (Revija za elementarno izobraževanje, 2024)
Intentional bilingualism is becoming increasingly popular in EFL countries, where many second-language speakers of English raise their children as a bilingual, with English alongside the local language. This article explores a case of intentional bilingualism spanning the first four years of a child, Ipek, who lives in Türkiye and has been exposed to Turkish and English since birth. As part of a longitudinal qualitative study, field and reflective notes were analysed to outline the key elements of Ipek’s context, including the participants, tools, methods and techniques. The insights and experiences gained in the study may contribute to developing effective strategies for intentional bilingualism.
Keywords: intentional bilingualism; Child bilingualism; Family language policy; EFL; Turkish as L1